2014
DOI: 10.5194/hess-18-1835-2014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial controls on groundwater response dynamics in a snowmelt-dominated montane catchment

Abstract: Abstract. The role of spatial variability in water inputs on runoff dynamics has generally not received as much research attention as topography and soils; however, the influence of topography and forest cover on snow surface energy exchanges can result in asynchronous snowmelt throughout a catchment, complicating the space–time patterns of runoff generation. This study investigates temporal variation in the relative importance of spatial controls on the occurrence, duration, and timing of shallow groundwater … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 77 publications
2
30
0
Order By: Relevance
“…Differentiating between the impact of the trenching location and the flat terrain is difficult because of the overlap in these terrain characteristics. This is consistent with Smith, Moore, Weiler, and Jost (), who found that the spatial distribution of inputs, in their case snow melt, is an important control on stream response.…”
Section: Discussionsupporting
confidence: 91%
“…Differentiating between the impact of the trenching location and the flat terrain is difficult because of the overlap in these terrain characteristics. This is consistent with Smith, Moore, Weiler, and Jost (), who found that the spatial distribution of inputs, in their case snow melt, is an important control on stream response.…”
Section: Discussionsupporting
confidence: 91%
“…However, the correlation decreased during rainfall events, becoming weakest in the largest events. This is consistent with the effects of rainfall input, limited storage and surface flow redistribution overwhelming the normal topographic controls (Smith et al, 2014). This is somewhat different to recent work by Rinderer et al (2014) who found in a pre-alpine catchment dominated by subsurface storm flow that correlations were strongest when GW levels were high and changed slowly, e.g.…”
Section: Dominant Landscape Controls On Groundwater Contributionssupporting
confidence: 85%
“…However, the correlation decreased during rainfall events, becoming weakest in the largest events. This is consistent with the effects of rainfall input, limited storage and surface flow redistribution overwhelming the normal topographic controls (Smith et al ., ). This is somewhat different to recent work by Rinderer et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, for a better understanding of runoff generation processes and runoff source area dynamics, the groundwater response during events is more relevant than during the recession or baseflow periods. To avoid the bias toward low flows, it is useful to apply the Flow‐corrected Time Transformation [ Rodhe et al ., ; Smith et al ., ]. In our case this involved stretching the time axis of the specific discharge time series, measured at the catchment outlet, proportional to the specific discharge during periods with above‐average specific discharge, and shrinking the time axis for all periods with below‐average specific discharge (Figure b).…”
Section: Methodsmentioning
confidence: 99%